2022
DOI: 10.1155/2022/3604012
|View full text |Cite|
|
Sign up to set email alerts
|

Edge Detection Algorithm-Based Lung Ultrasound in Evaluation of Efficacy of High-Flow Oxygen Therapy on Critical Lung Injury

Abstract: The study focused on the therapeutic effects of high-flow oxygen therapy on patients with critical lung injury using edge detection-based ultrasound images. Firstly, the traditional Canny edge detection algorithm was improved, and the optimal threshold was obtained by optimizing the median filter and combining Otsu algorithm and threshold iteration method. Then, the optimized algorithm was compared with the traditional Canny edge detection algorithm and applied to process the lung ultrasound images of 120 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Two thresholds were chosen as T1 and T2 (that is T2 is the major edge and T1 is a minor edge) such that (T1<T2) to obtain the binary image. Edge segments of T2 were linked to obtain the continuous edges and any that was below T2 and was greater than T1 that lies along the continuous T2 edge segments was consider a major edge [16].…”
Section: Double Thresholdingmentioning
confidence: 99%
“…Two thresholds were chosen as T1 and T2 (that is T2 is the major edge and T1 is a minor edge) such that (T1<T2) to obtain the binary image. Edge segments of T2 were linked to obtain the continuous edges and any that was below T2 and was greater than T1 that lies along the continuous T2 edge segments was consider a major edge [16].…”
Section: Double Thresholdingmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%